Kesulitan Siswa Dalam Mempelajari Jaring-Jaring Bangun Ruang Dan Luas Permukaan - Apriani Sinuraya, Rika; Nabilah, Nabilah; Anandita Nasution, Almira; Anandita Nasution, Vitri; Nabilla, Nabilla; Nurhudayah, Nurhudayah (Jurnal Pendidikan Tambusai, 2024)
Mathematics education is an important and significant component of formal education,playing a crucial role in human life. The teaching of mathematics spans from primary school to higher education, it's a fundamental component of the curriculum. Among the topics taught in elementary school mathematics is solid geometry, which is analyzed to provide students with an understanding of problem-solving in real-life situations. By introducing problems in the form of stories, students can gain insights and choose strategies to solve problems.This research aims to examine the challenges encountered by fifth-grade students when tackling narrative-based mathematical problems. related to solid geometry. These story problems are designed to assess students' understanding of applying solid geometry concepts in real-life contexts. Additionally, interviews with students the studies were carried out the alteration of weather patterns due to global warming is having a profound impact on agriculture around the challenges they encountered while solving these story problems. To enhance students' understanding of solving story problems related to solid geometry, it is recommended that teachers employ a contextual and visual teaching approach. Exercises involving the application of solid geometry concepts in everyday life should be provided to help students comprehend the relevance and practicality of these concepts. Moreover, it is crucial for teachers to offer clear guidance and support to students in understanding the instructions provided in the story problems.